2022
DOI: 10.1161/hypertensionaha.122.19280
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety and Effectiveness of Aldosterone Antagonists Versus Beta-Blockers as Fourth Agents in Patients With Apparent Resistant Hypertension

Abstract: BACKGROUND: Limited evidence exists regarding long-term effectiveness and safety of aldosterone antagonists (AAs) versus beta blockers (BBs) as fourth-line antihypertensive agents in patients with resistant hypertension (RH). We evaluated the comparative effectiveness and safety of aldosterone AA versus BB. METHODS: We conducted a real-world retrospective cohort study using IBM MarketScan commercial claims and Medicare Supplemental claims (2007–2019). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Finally, and most importantly, outcome RCTs in resistant hypertension are lacking. A recent real-world-evidence study in the United States included a total of 80 598 patients with resistant hypertension and compared the effectiveness of newly prescribed MRA treatment (6626 patients, 98% of whom were spironolactone users) with newly prescribed BB treatment (73 972 patients) as fourth line drugs [750]. In propensity score matched analysis, a 23% nonsignificant (95% CI 0.50– 1.19) reduction in favor of spironolactone for the combined primary outcome of stroke and myocardial infarction was found.…”
Section: True Resistant Hypertensionmentioning
confidence: 99%
“…Finally, and most importantly, outcome RCTs in resistant hypertension are lacking. A recent real-world-evidence study in the United States included a total of 80 598 patients with resistant hypertension and compared the effectiveness of newly prescribed MRA treatment (6626 patients, 98% of whom were spironolactone users) with newly prescribed BB treatment (73 972 patients) as fourth line drugs [750]. In propensity score matched analysis, a 23% nonsignificant (95% CI 0.50– 1.19) reduction in favor of spironolactone for the combined primary outcome of stroke and myocardial infarction was found.…”
Section: True Resistant Hypertensionmentioning
confidence: 99%
“…One major safety concern in MRA therapy is hyperkalemia, especially in patients with impaired renal function and/or with concomitant RAAS blockade. A recent published retrospective cohort study indicated that initiation of an MRA for resistant hypertension substantially increased the risk of hyperkalemia (57). Especially in CKD patients, hyperkalemia may restrict the access to MRA therapy, while co-treatment with diuretics may limit hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…96 Real-world evidence from the US comprising more than 80,000 patients with RH found a non-significant reduction in the rates of stroke and MI in patients taking spironolactone compared to β-blockers as fourth-line treatment, though the risk of hyperkalaemia and kidney function worsening was significantly higher with the former. 97 The risk of hyperkalaemia with spironolactone is a cause for concern, particularly in patients with CKD taking RAAS blockers. According to current guidelines, spironolactone should be used with caution in patients with an eGFR <45 ml/min/1.73 m 2 when plasma potassium concentration is >4.5 mmol/l, as these were exclusion criteria in the PATHWAY-2 trial.…”
Section: Pharmacological Strategiesmentioning
confidence: 99%